PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK DAPAT MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VB SDIT INSAN UTAMA PEKANBARU - Rahmi, Elfi; Azriani, Nelda; Marhadi, Hendri; Hermita, Neni (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2018)
This study is based on the low learning student’s social science outcomes. The purpuse of this study is to improve the learning outcomes of IPS with the implementation of cooperative learning model type talking stick, each cycle of two meetings and one time test. This study was conduted on 23 subjects of primary school students’ in SDIT Insan Utama Pekanbaru. Result of this research obtained average student’s learning outcomes 76,73 with enough categories and on the second cycle student’s learning outcomes increase to 82,17 categorized well. This suggest that the cooperative model type talking stick can improve the learning outcomes of IPS on the Primary School Students